Genetic Etiology of Neonatal Diabetes Mellitus in Vietnamese Infants and Characteristics of Those With INS Gene Mutations - Ngoc, Can Thi Bich; Dung, Vu Chi; De Franco, Elisa; Lan, Nguyen Ngoc; Thao, Bui Phuong; Khanh, Nguyen Ngoc; Flanagan, Sarah E.; Craig, Maria E.; Hoang, Nguyen Huy; Dien, Tran Minh (Frontiers in Endocrinology, 2022)
Background Neonatal diabetes mellitus (NDM) is a rare (1:90,000 newborns) but potentially devastating metabolic disorder characterized by hyperglycemia combined with low levels of insulin. Dominantly-acting insulin (INS) gene mutations cause permanent NDM through single amino acid changes in the protein sequence leading to protein misfolding, which is retained within the endoplasmic reticulum (ER), causing ER stress and β-cell apoptosis. Over 90 dominantly-acting INS gene mutations have been identified in individuals with permanent NDM. Patients and Methods The study included 70 infants diagnosed with NDM in the first year of life between May 2008 and May 2021 at the Vietnam National Children’s Hospital. Sequencing analysis of all the genes known to cause NDM was performed at the Exeter Genomic Laboratory, UK. Clinical characteristics, molecular genetics, and annual data relating to glycemic control (HbA1c) and severe hypoglycemia of those with INS mutations were collected. The main outcomes of interest were HbA1c, daily insulin dose, growth, and cognitive/motor development. Results Fifty-five of 70 infants (78.5%) with NDM harbored a mutation in a known disease-causing gene and of these, 10 had six different de novo heterozygous INS mutations. Mean gestational age was 38.1 ± 2.5 weeks and mean birth weight was 2.8 ± 0.5 g. They presented with NDM at 20 ± 17 weeks of age; 6/10 had diabetic ketoacidosis with pH 7.13 ± 0.26; plasma glucose level 32.6 ± 14.3 mmol/l and HbA1C 81 ± 15% mmol/mol. After 5.5 ± 4.8 years of insulin treatment, 9/10 have normal development with a developmental quotient of 80-100% and HbA1C 64 ± 7.3 mmol/mol, 9/10 have normal height, weight, and BMI on follow-up. Conclusions We report a series of Vietnamese NDM cases with dominant INS mutations. INS mutations are the third commonest cause of permanent NDM. We recommend screening of the INS gene in all children diagnosed with diabetes in the first year of life.